Development of Mathematical Snakes and Ladders Based Media Augmented Reality for Class V Students - Kistiyani, Alfina Dwi; Trisniawati, T; Muanifah, Mahmudah Titi; Silvianti, Fitrilia (Universitas Sarjanawiyata Tamansiswa, 2023)
This research was conducted in one of the elementary schools in the Wates, Kulon Progo area. This study aims to develop learning media based on snakes and ladders mathematics Augmented Reality for fifth grade students and describes the feasibility of mathematics-based snakes and ladders learning media Augmented Reality for fifth grade students. This development research uses the ADDIE development research model which is modified into three steps, namely Analysis, Design and Development. The methods used are qualitative methods and quantitative methods. The results showed that the learning media for snakes and ladders is mathematics based Augmented Reality meets the eligibility criteria as evidenced by the validation results of media experts getting an average score percentage of 99.57% with the